2018
DOI: 10.1097/inf.0000000000001715
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Fat and Lean Tissue With Whole Body and Spine Bone Mineral Density Is Modified by HIV Status and Sex in Children and Youth

Abstract: HIV disease diminishes the positive relationship of greater fat mass on bone mass in children/youth. Disruptions in body fat distribution, which are common in HIV disease, may have an impact on bone accretion during pubertal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition to that, studies that aimed to investigate the relationship between HIV infection/ART use and the health-related physical fitness components showed changes in the body fat distribution [91,104,194,264], reduction in the bone mass [15,84,108,124,209,262] and fat-free mass [8,102]. However, only 12.2% (n = 30) of the studies investigated more than one the health-related physical fitness component [21][22][23][24][25][26][27][28][29][30][31]33,34,41,47,50,52,106,110,112,116,192,196,[221][222][223]226,230,233,238] and no study that investigated the relationship between the health-related physical fitness components was found.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, studies that aimed to investigate the relationship between HIV infection/ART use and the health-related physical fitness components showed changes in the body fat distribution [91,104,194,264], reduction in the bone mass [15,84,108,124,209,262] and fat-free mass [8,102]. However, only 12.2% (n = 30) of the studies investigated more than one the health-related physical fitness component [21][22][23][24][25][26][27][28][29][30][31]33,34,41,47,50,52,106,110,112,116,192,196,[221][222][223]226,230,233,238] and no study that investigated the relationship between the health-related physical fitness components was found.…”
Section: Discussionmentioning
confidence: 99%
“…People living with HIV on newer non-thymidine NRTI regimens often develop simultaneous increases in both visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) [4,5]. The few studies that have quantified body mass composition in young people with HIV have also suggested increased fat and specifically trunk fat compared with uninfected young people [6][7][8]. With survival extending into adulthood, these findings suggest that alterations in regional fat are likely to continue to worsen over time and may contribute to cardiometabolic complications of HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, low BMD has recently been linked to disordered fat metabolism, possibly reflecting the common origin and interchangeability of bone and fat progenitor cells [61].…”
Section: Introductionmentioning
confidence: 99%